2018
DOI: 10.3390/ijerph15081788
|View full text |Cite
|
Sign up to set email alerts
|

Situational Use of Child Restraint Systems and Carpooling Behaviors in Parents and Caregivers

Abstract: Suboptimal compliance with child restraint system (CRS) recommendations can increase risk for injury or death in a motor vehicle crash. The purpose of this study was to examine scenarios associated with incomplete CRS use and non-use in children ages 4–10 years. We used a cross-sectional online survey with a convenience sample of parent/caregivers from the United States, age ≥18 years, with a child age 4–10 years in their home, who could read and spoke English, and drove child ≥6 times in previous three months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…For example, while 85.6 percent of participants reported that they 'always' restrained their youngest child in an appropriate restraint while travelling in their private motor vehicle, only 57.3 percent of participants reported that they 'always' restrained their youngest child in an appropriate restraint when they travelled in a rideshare vehicle. These findings are consistent with several studies from the United States who have recently noted that parents restrain their children 'differently' while travelling in alternative transport modes such as rideshare vehicles [6,19], taxis [16,18], or carpooling [17]. These findings have significant implications, suggesting that child occupants may be at an increased risk of death or serious injury in the event of a motor vehicle crash while travelling in these modes of transport.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, while 85.6 percent of participants reported that they 'always' restrained their youngest child in an appropriate restraint while travelling in their private motor vehicle, only 57.3 percent of participants reported that they 'always' restrained their youngest child in an appropriate restraint when they travelled in a rideshare vehicle. These findings are consistent with several studies from the United States who have recently noted that parents restrain their children 'differently' while travelling in alternative transport modes such as rideshare vehicles [6,19], taxis [16,18], or carpooling [17]. These findings have significant implications, suggesting that child occupants may be at an increased risk of death or serious injury in the event of a motor vehicle crash while travelling in these modes of transport.…”
Section: Discussionsupporting
confidence: 90%
“…Although child restraint use is high (i.e., over 90%) in private motor vehicles in Australia [13][14][15], research has shown that child restraint use is substantially lower in shared transportation modes such as taxis, rideshare vehicles and carpooling [6,[16][17][18][19]. For example, in the United States, Owens and colleagues [6] reported that 59 percent of parents restrained their children aged five years and younger 'differently' when travelling in a rideshare vehicle than they did when travelling in their private motor vehicle, including holding the child on their lap (37.0%) or letting their child travel without an appropriate child restraint (25.0%).…”
Section: Introductionmentioning
confidence: 99%
“…This finding indicates that if the parents' close friends have positive attitudes toward CRS use, the parents are also likely to use a CRS. This may be attributed to the effect of social norms, which are highly associated with CRS use [76].…”
Section: Structural Modelsmentioning
confidence: 99%
“…The target population is unable to behave in such situations and requires marketing strategies to address the same. 20 21 Social marketing is an innovative platform to bring about desired behavior change. As one has to manage his/her life with SARS-CoV-2, the expected behavior change has to be long term at individual, group, or organizational and societal levels.…”
Section: Reviewmentioning
confidence: 99%